HIDROLISIS IKAN BERNILAI EKONOMI RENDAH SECARA ENZIMATIS MENGGUNAKAN PROTEASE BIDURI [Enzymatic Hydrolysis of the Low Economic Value Fishes using Biduri’s Protease] - Yuli Witono; Iwan Taruna; Wiwik Siti Widrati; Amelia Ratna (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
Fish protein hydrolyzate is a product obtained from the decomposition of fish proteins into short-chain compounds due to the hydrolysis process either by enzymes, acids, or bases. The purpose of this study was to optimize the production of fish protein hydrolyzate from the low economic value fishes including 'bibisan' (Apogon albimaculosus), 'baji-baji' (Platycephalidae cymbacephalus), and the 'lidah' (Cynoglossus lingua) taken from Talango Island, Madura. The production of fish protein hydrolyzate used enzymatic hydrolysis by biduri’s (Calotropis gigantea) protease. The concentrations of biduri’s protease varied (0, 0.7, 1.4, and 2.1 Unit/g) and at various hydrolysis times (0, 1.5, and 3 h). The experimental design was a Completely Randomized Design with two factors which were carried out in triplicates. The results showed that interactions between the protease concentrations and times significantly affected (at 5% level test) the soluble proteins, maillard products, and the level of rancidity measured as thiobarbituric acid (TBA). The best fish hydrolyzate product based on the soluble protein parameter was resulted from 2.1 Unit/g biduri’s protease and hydrolysis time of 1.5 h. The characteristics of the hydrolyzate were containing 3.51% of soluble proteins, having maillard value of 0.63, and rancidity levels of 12.21 mmol TBA/kg.